CCAFS Deep Dive Assessment of Climate-Smart Agriculture (CSA) in the Feed the Future Portfolio in Senegal - Bonilla Findji, Osana; Zougmoré, Robert B.; Henry, Kevin; Schreeg, Laura; Jarvis, Andy (2016)
As part of a global effort that will inform how Feed the Future tracks CSA across the 19 focus countries (plus aligned) the CCAFS and USAID/BFS team selected 5 to carry out a deeper analysis of their portfolio. In July 2015, CCAFS’ visit to the USAID Senegal mission provided an opportunity to identify and discuss CSA-related activities within the country and the USAID zone of influence (ZOI) highlighting the importance of addressing the effects of climate change in the agricultural sector and the current and potential benefits of Feed the Future’s presence for climate resilience. The visit included meetings with USAID Mission staff, Feed the Future implementing partners, and three government agencies. The process also included the review of Feed the Future strategy and project documents, as well as a limited external literature review. This report outlines the key findings of the visit and highlights some ways in which CSA approaches can be further incorporated into the Mission’s future programming.